2023
DOI: 10.1007/s10479-023-05185-w
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of variables methods and measurement models for soccer players’ performances

Abstract: In sports, studying player performances is a key issue since it provides a guideline for strategic choices and helps teams in the complex procedure of buying and selling of players. In this paper we aim at investigating the ability of various composite indicators to define a measurement structure for the global soccer performance. We rely on data provided by the EA Sports experts, who are the ultimate authority on soccer performance measurement: they periodically produce a set of players’ attributes that make … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Professionals must apply appropriate methods to pinpoint and select key performance indicators once data has been collected in each session 2 , 11 . In this regard, resent research suggested the use of Partial Least-Squares Structural Equation Model (PLS-SEM) to measure performance 12 , 13 . Utilizing freely accessible key performance indicators sourced from sofifa.com, previous research developed composite indicators for mobile players in the top 5 European Leagues using a Third Order PLS-SEM model, albeit without considering physical performance 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Professionals must apply appropriate methods to pinpoint and select key performance indicators once data has been collected in each session 2 , 11 . In this regard, resent research suggested the use of Partial Least-Squares Structural Equation Model (PLS-SEM) to measure performance 12 , 13 . Utilizing freely accessible key performance indicators sourced from sofifa.com, previous research developed composite indicators for mobile players in the top 5 European Leagues using a Third Order PLS-SEM model, albeit without considering physical performance 12 .…”
Section: Introductionmentioning
confidence: 99%